TEKNOLOGI SEBAGAI SAHABAT BELAJAR: MENGGALI POTENSI DAN MENGATASI TANTANGAN DALAM PEMEROLEHAN BAHASA PADA ANAK USIA DINI - Erra Yuni Rindiani; Lina Putrianti (STKIP Subang, 2024)
The integration of technology in early childhood language acquisition poses both challenges and opportunities. This study investigates how digital tools can support or hinder language development among young children. The primary objective is to identify effective technological strategies that facilitate linguistic growth and to assess potential drawbacks. Methodologically, this research adopts a mixed-methods approach, combining quantitative surveys with preschool educators and qualitative interviews with parents. Additionally, digital interaction sessions with children were analyzed to observe real-time responses and engagement levels with language-learning technologies. The findings reveal that while technology, such as interactive apps and virtual story sessions, significantly enhances vocabulary acquisition and engagement levels, excessive screen time and poorly designed content could potentially delay language development. The study highlights the importance of curated content and the role of caregivers in moderating technology use. Recommendations are provided for developing age-appropriate, linguistically enriching technological resources that can effectively support early language learning without overwhelming young learners. The research contributes to the ongoing dialogue on educational technology by delineating key factors that ensure the beneficial use of digital tools in early childhood language acquisition.